2019
DOI: 10.1177/1049909119864025
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultation Is Underutilized in Critically Ill General Surgery Patients

Abstract: Background: American College of Surgeons recommends palliative care and surgeons collaborate on the care of patients with poor prognoses. These collaborations are done to discuss symptom management and goals of care. However, contemporary practice patterns of palliative care consultation for surgical patients are poorly defined. We aim to describe the use of palliative care consultation for patients admitted to our institution’s surgical services who died during their index hospital admission. Methods: The Duk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…Given that less than 3% of all patients in this study had a specialised palliative care team involved, one might wonder whether more involvement from specialised palliative care teams would have increased the overall care quality. To compare, in a study by Evans et al, 37% of critically ill general surgery patients received a palliative care consultation and this was considered underutilisation (29).…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that less than 3% of all patients in this study had a specialised palliative care team involved, one might wonder whether more involvement from specialised palliative care teams would have increased the overall care quality. To compare, in a study by Evans et al, 37% of critically ill general surgery patients received a palliative care consultation and this was considered underutilisation (29).…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…Given that less than 3% of all patients in this study had a specialised palliative care team involved, one might wonder whether more involvement from specialised palliative care teams would have increased the overall care quality. To compare, in a study by Evans et al, 37% of critically ill general surgery patients received a palliative care consultation and this was considered underutilisation ( 29 ). The availability to, and organisation of, specialised palliative care varies in Sweden ( 4 ), and the pre-pandemic referral of nursing home residents to specialised palliative care was uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is evidence that, in the past, palliative care consultation was underutilized in the care of critically ill general surgery patients. 15 In the geriatric trauma population, palliative care remains underutilized among patients dying within 6 months after discharge. 16 Early goals of care discussions and multidisciplinary family meetings are associated with increased comfort care measures for imminently dying trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients admitted with gastrointestinal or thoracic malignancies undergoing surgery were 79% less likely to receive PC consultation than patients who did not undergo surgery during their inpatient admission (36). Likewise, Evans and coauthors found that PC consultation was requested in only 37% of cases where critically ill general surgery patients died during hospital admission (37). Aslakson et al reviewed 37 publications that addressed the evidence base of thirty PC interventions in the ICU.…”
Section: An Unmet Needmentioning
confidence: 99%